Analysis of Instrument Development Recount Text Writing Test HOTS for Vocational High School using Exploratory Factor Analysis (EFA) - Muhammad Haris Setiawan; Supriyadi Supriyadi; Dwi Anggani L. Bharati (Universitas Negeri Makassar, 2022)
This study aims to determine the construct validity and reliability of the instrument recount text writing test HOTS in English subjects for vocational high school students. This method used a development research design from Djemari Mardapi which has been modified with the three steps. The analysis of construct validity instrument is based on how many factors are needed to explain the relationship between a set of indicators and is used the SPSS Statistic v24 application and reliability used Cronbach's Alpha. The sample in this study were 30 students with a quota sampling approach and were taken randomly. The results of the analysis construct validity with EFA got KMO values > 0.5, Anti Image Correlation > 0.5, Eigenvalue 1 and Factor Loading 0.3 and instrument reliability is 0.771. The results showed that overall, the items of instrument recount text writing test HOTS in English subjects for vocational high school students had good construct validity scores, all items were able to measure every cognitive ability and showed that the construct validity of each test item developed was good because of construct validity. Teachers need to use the development of this standard instrument to reduce the level of subjectivity of the assessment. Teachers should start using learning models and include HOTS questions to improve students' thinking skills.